PRIMARY MEDICAL PREPARATION IN THEOLOGICAL COLLEGES OF PRE-REVOLUTIONARY RUSSIA - Anna D. Avdeeva (Высшее образование в России, 2016)
Basing on information taken from the Account of the synodal Ober-prosecutor (1905-1914), the author investigates how medicine and hygiene were introduced into the programmes of theological colleges. Here is given the description of holding lessons on these subjects, including drunkenness-prevention lectures. The main conclusion contains the assertation that such preparation of seminarists influenced positively on public health of pre-revolutionary Russia.